Pectin functionalized with Cu/Fe nanoparticles for enhanced degradation of methylene blue from wastewater - Hassan, Faiza; Talib, Usama; Saif, Sadia; Akhter, Parveen; Ali, Faisal; Abbas, Moneeza; Younas, Umer; Ashraf, Kamran; Alamri, Saud; Zaman, Qamar uz (Frontiers in Sustainable Food Systems, 2024)
In present study, citrus pectin stabilized Copper/ Iron bimetallic nanoparticles catalyst has been used for the degradation of methylene blue dye in food industry wastewater. The P@Cu/Fe composites were synthesized by co-precipitation and sol gel methods. Characterization of the composites was carried out employing UV, FTIR, SEM & XRD techniques revealing that P 1 @Cu/FeNPs synthesized through co-precipitation came up with particle size of 150nm-35nm and having irregular spherical and hexagonal shape. P 2 @Cu/FeNPs, synthesized via gel combustion method using triethylamine as fuel, proved to be a better nanocatalyst with spherical particles having uniform structure and size distribution of 105nm-23nm. Mean zeta potential value of P 1 @Cu/FeNPs found to be between 0-5mv showing the composite less stable and 13mv for more stable P 2 @Cu/FeNPs. Degradation of methylene blue by P 1 @Cu/FeNPs was recorded up to 23.57% after 35min and nanocomposite synthesized by sol gel method exhibited 97.28% degradation in 30 min. The P 2 @Cu/FeNPs performed best degradation due to its synergistic impact. In essence, this research represents a step towards the synthesis of bimetallic nanoparticles employing a biomaterial (citrus pectin) with improved synergistic photocatalytic potential that can induce different features to nanomaterials. Pectin functionalized nanoparticles using different metals should be synthesized and tested for different catalytic applications.